Left Paraduodenal Hernia Successfully Treated with Laparoscopic Surgery: A Case Report - Shoji, Tuyoshi (S. Karger AG, 2007)
A 60-year-old Japanese man was referred for examination of abdominal pain. Abdominal MRI exactly demonstrated paraduodenal hernia. Propylthiouracil was administered until the patient became euthyroid, because Graves' disease was detected during the subsequent general examinations. Laparoscopic repair was then carried out. The sac collar, which had a diameter of about 30 mm, was located lateral to the ascending portion of the duodenum. Bowel incarcerated in the hernia sac was reduced and the hernia orifice closed. The postoperative course was good, and the patient was discharged 7 days after surgery. The diagnosis by MRI has made possible laparoscopic surgery for paraduodenal hernia.